Strategi Pemasaran Internasional Somethinc dalam Memasuki Pasar Skincare Malaysia dan Singapura: Studi Kualitatif - Septiani Margianti; Widya Saputri; Rindiana Ridwansyah; Mohamad Zein Saleh (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to explore the international marketing strategies implemented by Somethinc, an Indonesian local skincare brand, in entering the Malaysian and Singaporean markets. Using a qualitative approach through library research, the study analyzes secondary data from scientific journals, market reports, online articles, and official brand documents. The findings reveal that Somethinc adopts an adaptive and digital-based marketing approach, which includes product localization, halal and cruelty-free branding, and intensive use of social media platforms to engage with local consumers. Key challenges identified include fierce competition with established international brands, regulatory complexities, and consumer preference differences. Nonetheless, Somethinc’s ability to align its brand positioning with local cultural values and consumer behavior has contributed to positive consumer perception and growing brand visibility. The study offers valuable insights for other local beauty brands seeking to expand regionally by emphasizing cultural adaptation, strong digital presence, and brand authenticity.